Nuclear receptors in health and disease: signaling pathways, biological functions and pharmaceutical interventions - Ping Jin; Xirui Duan; Zhao Huang; Yuan Dong; Jianmei Zhu; Huiming Guo; Hui Tian; Cheng-Gang Zou; Ke Xie (Signal Transduction and Targeted Therapy)
Abstract Nuclear receptors (NRs) are a large family of ligand-dependent transcription factors that regulate the expression of a wide range of target genes in response to endogenous and exogenous ligands, including steroid hormones, thyroid hormone, vitamin D, retinoic acid, fatty acids, and oxidative steroids. Upon ligand binding, nuclear receptors form dimer complexes with transcriptional cofactors, which interact with specific DNA sequences in the promoter or enhancer regions of target genes to modulate gene expression. This process plays a crucial role in many physiological processes such as reproduction, development, immune responses, metabolism, and homeostasis. Dysregulation of nuclear receptor signaling is implicated in the pathogenesis of numerous diseases, including cancers, metabolic disorders, cardiovascular diseases, and autoimmune conditions. Therefore, understanding the molecular mechanisms underlying nuclear receptor functions is essential for the development of novel therapeutic strategies. This review summarizes the current understanding of nuclear receptors in both physiological and pathological contexts, providing insights into the signaling pathways they regulate. Additionally, we discuss recent advances in drug development targeting nuclear receptors, with a focus on preclinical and clinical studies aimed at improving therapeutic efficacy. By exploring these therapeutic avenues, this article highlights the potential of nuclear receptors as promising targets for future treatments of a variety of human diseases, paving the way for more personalized and effective therapies in clinical medicine.